2020
DOI: 10.3390/min10020123
|View full text |Cite
|
Sign up to set email alerts
|

The Behaviour of Mixtures of Sodium Iso-Butyl Xanthate and Sodium Di-Ethyl Dithiophosphate during the Flotation of a Cu-Ni-Pt Ore in Degrading Water Quality

Abstract: The use of mixtures of thiol collectors is reportedly beneficial in sulfide flotation. This is becoming standard practice for many concentrators, but process water recirculation and re-use in flotation circuits may compromise the behaviour of such mixtures owing to changes in physicochemical interactions occurring in the pulp phase as a result of water quality variations. It is expected that changes in the pulp chemistry would in turn affect both the pulp and froth phase phenomena, thereby affecting flotation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…A 1 kg amount of a Merensky ore sample was milled at 66% solids in single-salt solutions in order to obtain a grind of 60%, passing 75 µm for 13.5 min, as determined by the milling curve shown in [4], for each experimental test. The milled sample was transferred into a 3 L Barker flotation cell.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A 1 kg amount of a Merensky ore sample was milled at 66% solids in single-salt solutions in order to obtain a grind of 60%, passing 75 µm for 13.5 min, as determined by the milling curve shown in [4], for each experimental test. The milled sample was transferred into a 3 L Barker flotation cell.…”
Section: Methodsmentioning
confidence: 99%
“…This was attributed to better surface coverage with mixed thiol collectors and, therefore, better hydrophobization. Thiol collectors such as dithiophosphates (DTP) and xanthates are said to have the ability to increase hydrophobicity and are also classified as good froth stabilizing agents [1][2][3][4]. These attributes of most thiol collectors result in recoveries of heterogeneous minerals such as base metal sulfides and may also result in high solids recoveries of both fine and coarse interlocked particles owing to a possible increase in froth stability [2,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study by Manono et al maintained the ionic strength of various single salt solutions constant at 0.0213 M. This ionic strength could possibly be very low to see the effect of specific ions on mineral recoveries as the ionic strength of plant water used on a concentrator was shown to be closer to 0.0723 and 0.1205 M . Following Manono et al, oxyhydroxo species were considered on a similar sulfidic copper and nickel ore in a different study; it was shown that operating at pH 11 resulted in a decrease in copper and nickel recoveries, suggesting that the floatabilities of copper (chalcopyrite) and nickel (pentlandite) were impeded.…”
Section: Introductionmentioning
confidence: 99%
“…As this study specifically considers the bubble–particle attachment of pyrrhotite in specific inorganic electrolytes found in process water, building on the work of Manono et al, , it was speculated that pyrrhotite would be of interesting consideration owing to its rather peculiar surface chemistry. A number of studies on the behavior and floatability of pyrrhotite against different pulp chemistry have been conducted. It is important to note that pyrrhotite is an iron sulfide mineral with the formula Fe (1 – x ) S, where 0 < x ≤ 0.125; this results in many pyrrhotite superstructures.…”
Section: Introductionmentioning
confidence: 99%